Effects of a High-Protein Corn Co-product as a Replacement for Soybean Meal in Calf Starter Grains - R. G. Skinner; W. E. Brown (Kansas Agricultural Experiment Station Research Reports, 2025)
The objective of this study was to assess the effects of replacing soybean meal with a novel high-protein corn co-product (HPCC) as a protein source in dairy calf starter grains. Forty-two Holstein calves were blocked by sex and birthdate and assigned to one of three starter grain treatments offered from 14 to 84 days of age. Assigned diets replaced 0 (CTRL), 50 (50HPCC), or 100% (100HPCC) of the soybean meal (16.6% of dietary dry matter (DM)) with HPCC. Supplemental methionine and lysine were added to starters as needed so that all diets met the theoretical requirements for limiting amino acids in young calves. Calves were fed waste milk based on birth weight until initiation of step-down weaning at 42 days of age, with all calves being completely weaned by 56 days of age. Weights, growth measurements, and blood samples were obtained for each calf every 14 ± 1 day. Fecal samples were collected from each calf on the last four days of the study to determine diet digestibility. Inclusion of HPCC quadratically affected starter grain intake during the preweaning period (14 to 41 days of age), with 100HPCC calves consuming the most and 50HPCC calves consuming the least. However, provision of HPCC increased preweaning body weight, and there was no evidence that HPCC treatment affected feed efficiency. After weaning (56 to 84 days of age), calves tended to consume more starter grain as HPCC inclusion increased. Body weight and average daily gain (ADG) increased with increasing HPCC inclusion. Wither height was reduced for 50HPCC calves compared to 100HPCC calves, but HPCC inclusion did not affect any other measures of structural growth. Apparent total tract digestibility of DM and crude protein (CP) tended to be greater for the HPCC diets than CTRL. In conclusion, results suggest that HPCC is a suitable replacement for soybean meal in starter grains that have been balanced for methionine and lysine supply.
Keywords: calf nutrition; starter grains; byproducts